The effect of pre-sowing seed treatment and foliar feeding on the formation on air-dry mass of sunflower plants (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The results of two-year studies on the complex effect of various options for pre-sowing seed treatment and foliar feeding with various combinations of reactivating drugs on the dynamics of air-dry mass formation of high-oleic sunflower hybrid AVRORA AM have been highlighted.Formulation of the problem. The effectiveness of sunflower production is limited by adverse weather conditions characteristic of this area, namely: rainfall deficit, long periods without rain and elevated temperature indicators – over 27 ºC. In addition, the negative impact of these factors is gradually increasing. During the last period, factors capable of reducing the negative impact of stress factors during sunflower cultivation were determined. In this regard, the role of pre-sowing seed treatment and foliar fertilization with stimulants capable of enhancing the growth of roots and above-ground vegetative biomass, increasing the resistance of plants to abiotic factor and contributing to increasing their seed productivity is increasing.The purpose of the research was to study the influence of seed treatment with drugs of multidirectional action (growth stimulators, mycorhizal products) and foliar fertilization with mixture of growth stimulators in combination with modern water-soluble fertilizers on the formation of air-dry mass indicators of high-oleic sunflower hybrid – AVRORA AM.Research methods. The research was conducted in 2022 and 2023 on the basis of LLC «Alliance Agro» in the Pyryatinsky district of the Poltava region. To solve the tasks, a two-factor field experiment using the method of split plots was laid. The plots of first order were six variants of pre-sowing seed treatment, the second order – seven variants of foliar feeding. The total number of options in the experiments is 42. The area of the sowing and accounting plots of the experiment was 105.0 and 84.0 m2, respectively.   Research results. The high efficiency of pre-sowing seed treatment with a mixture of the growth stimulator Black Jack, the mycorrhiza-forming drug Mycofriend and the bacterial drug «PMK-U» and carrying out two foliar feeding – during the 12-13th and 35-37th micro phases for the intensity of growth of air-dry mass of sunflower plants was established. In the studied micro phases – the 51st (asterisk), the 61st (beginning of flowering) and the 80th (beginning of seeding), the air-dry mass of one sunflower plant compared to the control, in these variants was 11.9 %, 12.2 and 13.3 % higher.The air-dry mass of plats per 1 m2 was also greater on these options. In particular, in the phases of the star, the beginning of flowering and the beginning of pouring seeds, it was 161.0 g/m2, 441.0 and 656.6 g/m2, respectively. The influence of the studied factors on the air-dry mass of sunflower plants from 1 m2 was higher than on the air-dry mass of one plant, which is associated with higher indicators of field germination of seeds and preservation of plants. Thus, the increase in the indicator compared to the control variant in the marked phases was 19.7 % (26.5 g), 20.1 % (73.9 g) and 22.4 % (120.3 g), respectively, which is a significantly higher increase in air-dry mass of the plant.Conclusions. Carrying out two foliar feeding in terms of the effect on the air-dry mass of plants was actually on the same level as the variants of three feedings. The difference between the indicators of air-dry mass did not exceed 2.7 %. Therefore, taking into account the absence of a significant difference between these options in terms of air-dry mass of sunflower plants both from a unit area and from one plant, as well as taking into account less soil compaction due to the reduction of aggregate passes and lower economic costs, the optimal option should be considered seed treatment with a mixture of Mycofriend, Black Jack and «PMK-U», followed by two foliar feeding with a mixture of Black Jack growth stimulator (Alhum Plus) with water-soluble fertilizers of the Jiva MIX line in recommended doses.
Keywords: sunflower; hybrid; seed treatment; foliar feeding; growth stimulants; mycorhizal and bacterial preparations; air-dry mass of plants